2015
DOI: 10.1002/gj.2749
|View full text |Cite
|
Sign up to set email alerts
|

K–Ar mineral ages and thermal history of magmatic and metamorphic Palaeoproterozoic units from the northern part of Kedougou Kenieba Inlier, West African Craton (Eastern Senegal)

Abstract: The northern part of the Kedougou Kenieba Inlier (Eastern Senegal) is composed of Palaeoproterozoic volcano-plutonic and volcanosediment areas cross-cut by differentiated plutonic bodies of gabbroic to granitic composition. They are emplaced in an arc-type environment and accreted during the Eburnean Orogeny. We present here new K-Ar ages obtained on several plutons from different mineralogical phases, each characterized by a different closure temperature for the K-Ar system. Ages from hornblende, between 2013… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 28 publications
(42 reference statements)
2
3
0
Order By: Relevance
“…New 40 Ar/ 39 Ar ages obtained here on hornblendes and biotites range within 2028 ± 14 and 2055 ± 10 Ma (Table 1), with a mean age of about 2040 Ma. Comparison with previous K-Ar ages realized on the same samples (Sagna et al, 2017) shows that the 40 Ar/ 39 Ar ages obtained here are more clustered and some are significantly older. This could be explained by the fact that the K-Ar technique is unable to detect loss of radiogenic argon from the less retentive sites during thermal events (e.g., McDougall and Harrison, 1999).…”
Section: Cooling Temperatures Of the Granitoidssupporting
confidence: 75%
See 2 more Smart Citations
“…New 40 Ar/ 39 Ar ages obtained here on hornblendes and biotites range within 2028 ± 14 and 2055 ± 10 Ma (Table 1), with a mean age of about 2040 Ma. Comparison with previous K-Ar ages realized on the same samples (Sagna et al, 2017) shows that the 40 Ar/ 39 Ar ages obtained here are more clustered and some are significantly older. This could be explained by the fact that the K-Ar technique is unable to detect loss of radiogenic argon from the less retentive sites during thermal events (e.g., McDougall and Harrison, 1999).…”
Section: Cooling Temperatures Of the Granitoidssupporting
confidence: 75%
“…Recent K-Ar ages, performed on hornblende, biotite and K-feldspar minerals from the same samples as those investigated in the present study, have shown that plutonism in the Kedougou Kenieba Inlier occurred between 2.0 and 2.1 Ga, and suggested either a slow cooling rate for hundreds of Ma, or that a thermal event partially re-opened the K-Ar system of K-feldspars from this area (Sagna et al, 2017).…”
Section: Kedougou Kenieba Inlier (Kki)supporting
confidence: 62%
See 1 more Smart Citation
“…One Ar determination was conducted in K-feldspar of the samples for preliminary purposes, as K-Ar ages on such phases generally provide inconclusive information regarding granite crystallization age at depth due to their poor Ar retentivity at high temperature (e.g. Sagna et al, 2017). However, K-feldspar can be used to achieve a thermochronological analysis through step-heating 40 Ar/ 39 Ar (see next section, and Lovera et al, 1997;Sagna et al, 2021).…”
Section: K-ar and 40 Ar/ 39 Ar Datingmentioning
confidence: 99%
“…The air aliquot used to calibrate the 40 Ar measurements is calibrated by routine measurements of the interlaboratory standard HD-B1 (Fuhrmann et al, 1987). This technique is suitable for dating into the last millennia (Gillot et al, 2006;Quidelleur et al, 2001), as well as into the pre-Cambrian (Sagna et al, 2017). Note that for old samples determination, the total relative age uncertainty is 1.4% and is calculated as the quadratic sum of the 1% uncertainties attached to both the K content determination and the 40 Ar calibration, the radiogenic argon content uncertainty being negligible.…”
Section: New K-ar Ages On Separated Mineralsmentioning
confidence: 99%